The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1152/ajpendo.1993.264.2.e285
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine redirects metabolism and prevents seasonal onset of obese hyperinsulinemic state in Syrian hamsters

Abstract: Bromocriptine redirects metabolism and prevents seasonal onset of the obese hyperinsulinemic state in Syrian hamsters. Metabolic and hormonal effects of bromocriptine were studied in seasonally obese female Syrian hamsters, Mesocricetus auratus. Daily injections of bromocriptine and vehicle (controls) were made at light onset (10:14-h light-dark cycle) for 10 wk. After 9 wk of treatment blood samples were taken every 4 h during a day for assays of hormones, glucose, triglyceride, and fatty acids, and after 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
62
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 36 publications
18
62
0
Order By: Relevance
“…Furthermore, gonadal function was not restored after 1 month of treatment in patients with prolactinomas. The observed reduction in leptin levels at 1 month without change in body weight or BMI may still be indicative of a loss in body fat which has been previously observed in experimental animals (10).…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, gonadal function was not restored after 1 month of treatment in patients with prolactinomas. The observed reduction in leptin levels at 1 month without change in body weight or BMI may still be indicative of a loss in body fat which has been previously observed in experimental animals (10).…”
Section: Discussionsupporting
confidence: 71%
“…29,30 Corticosterone is a potent stimulator of lipolysis, hepatic glucose output and lipogenesis, therefore, the substantial reduction of plasma corticosterone induced by the treatment (but not by pair feeding) may contribute to the reductions of these biochemical activities. The drug induced reduction in plasma T 4 concentrations seen in association with decreased body weight gain and increased oxygen consumption may seem paradoxical, however, similar associations have previously been reported with interventions which increase dopamine activities (such as BC treatment in the Syrian hamster 17 and dopamine B-hydroxylase knockout mice. 31 Since thyroid hormones induce hepatic lipogenic malic enzyme activity, and increase glucose output and lipolysis, the reduction of T 4 by BCaSKF (but not by pair feeding) correlates well with the above described treatment effects on metabolism.…”
Section: Dopaminergic Agonists Improve Diabetes In Obaob Micesupporting
confidence: 57%
“…BCaSKF treatment has been shown to increase protein mass in these mice 4 as has bromocriptine in hamsters. 17 The relatively high RQ values presented in Table 2 may be the result of the time of the day that the measurements were taken (at 2 ± 5 h after the onset of light). At this time of day, obaob mice have a low metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have consistently demonstrated the ability of such circadian-timed daily administration of bromocriptine (systemic or intracerebroventricular) to markedly reduce insulin resistance (particularly during the postprandial state [125,126], in agreement with its ability to improve VMH hypothalamic fuel-sensing mechanisms as described above), hyperinsulinemia and/or glucose intolerance without raising the plasma insulin level, in a variety of animal models of IRS including seasonal insulin-resistant hamsters, SHRs, high-fat fed rats, genetically leptin-deficient ob/ob mice, fattened pigs, and high-fat fed dogs [86,124,[126][127][128][129][130][131][132]. As a composite, these animal studies provide evidence that timed bromocriptine treatment improves dysglycemia by improving (postprandial) insulin action in the liver and/or peripheral insulin-sensitive tissues (e.g.…”
Section: Non-scn Cns Dopaminergic Activities Regulating Peripheral Mementioning
confidence: 81%